Ecological interactions and diversity of insects on Fabaceae species in the Brazilian Cerrado - Lopes, Bruno de Sousa (2020)
Insect-plant interactions are among the oldest, most diverse and complex biotic relationships, ranging from antagonisms (e.g., herbivory) to mutualisms (e.g., protection mutualism). Regarding the herbivory, we know that both bottom-up and top-down forces affect the occurrence of insect herbivores and the structure of terrestrial communities. However, it is not well understood how these selective forces change among herbivore guilds and environments, especially in tropical areas such as the Cerrado. In addition to being one of the most threatened biomes on the planet due to its rapid transformation into pasture and/or cash-crop agriculture, large Cerrado\'s botanical families such as Fabaceae has few information in relation to their interactions with insects. Thus, the general aims of this thesis were to: (1) characterize the community of arthropods, insect herbivores and their natural enemies, associated with the Fabaceae species commonly found in the Cerrado: Andira humilis, Bauhinia rufa, Chamaecrista cathartica, Mimosa setosa var. paludosa, and Stryphnodendron polyphyllum; and (2) evaluate the effects of bottom-up (plant traits) and top-down (spiders, ants and wasps) forces on the occurrence of insect herbivores. This thesis was divided in five chapters. In the Chapter 1, we described the insect herbivores, natural enemies, Fabaceaeherbivore network and community metrics such as Shannon-diversity index, specialization, modularity and robustness. We found 1623 insect herbivores belonging to five orders, 23 families and 87 species. Their main natural enemies were species of ants (n= 11), spiders (n= 01), hemipterans (n= 01), and parasitoid wasps (n= 03). The Fabaceae-herbivore network was modular, with only six species of insects feeding on more than one host plant species. In the Chapter 2, we chose the two most abundant insect herbivores as models, Acanthoscelides winderi and A. quadridentatus, and found that these beetles were responsible for the predation of about 15% of seeds produced by M. setosa var. paludosa. The attacked seeds did not germinate, and even the healthy seeds from infested fruits had worse germination rate than healthy seeds from noninfested fruits, suggesting a decrease in resource allocation by plants in attacked structures. Acanthoscelides winderi and A. quadridentatus were synchronized with the fruiting, but with a temporal partitioning in their occurrence, suggesting the avoidance of competition in order to maintain their coexistence. In the Chapter 3, we found that seed traits such as size, weight, hardness, and water content varied in a spatial (~240 km, four populations of M. setosa var. paludosa from Minas Gerais to Goiás) and temporal (fruiting period) scale, affecting the occurrence of these beetles. The body weight of A. quadridentatus was positively correlated with seed weight, length and water content. Larger and heavier seeds were most protected (hardness), but individuals of A. quadridentatus that had overcome seed hardness obtained larger sizes, being males and females 15 and 25% larger, respectively. In the Chapter 5, we showed that one of the main natural enemies found, Peucetia flava, decreased 3.3-fold the damage inflicted by insect herbivores on leaves of M. setosa var. paludosa. In addition, this spider also fed on insect carrion provided by the plant\'s glandular trichomes, which suggests a facultative mutualism. If on the one hand the spider was effective in protecting the plant against exophytic leaf herbivores, on the other hand it was unable to protect the plant against endophytic seed herbivores (e.g., A. winderi) since these beetles were able to defend themselves against the spider by hiding vulnerable body parts under their elytra. Consequently, the presence of spiders did not reduce the proportion of seeds taken by those beetles. Finally, we found a new species of parasitoid wasp in this system. Thus in the Chapter 5 we described Cotesia itororensis and notes on its impact on the host, Oospila pallidaria. The results of this thesis highlighted that the most abundant species of insect herbivores presented a pattern of high specificity and phenological synchronicity with their host plants. Both plant traits and natural enemies affected the results of interactions, the former changing traits of herbivores\' life history (e.g., size) and the latter decreasing their occurrence. We suggest conditionality in the interaction outcomes, which may vary spatiotemporally and depend on the guild and/or taxa of the insect herbivores. Furthermore, due to the high host plant specificity by insect herbivores, we suggest that is crucial the conservation of areas with huge plant diversity to maintain insects\' occurrence and their important roles in structuring terrestrial communities in Brazilian Cerrado. Making that it is also possible that more new species will be described, which will increases our knowledge about the Brazilian biodiversity.